Evaluation of the removal of impassable barriers on anadromous salmon and steelhead in the Columbia River Basin. (15th January 2020) - Clark, Christopher; Roni, Philip; Keeton, Jenna; Pess, George
Abstract: Despite the popularity of barrier removal as a habitat restoration technique, there are few studies that evaluate the biological effects of restored stream crossings. An extensive post‐treatment study design was used to quantify fish populations (e.g. species, life stage, abundance) and habitat attributes (e.g. gradient, geomorphic channel units) at 32 culvert removal or replacement projects to determine their effectiveness in restoring habitat access for juvenile salmon, Oncorhynchus spp., and steelhead, O. mykiss (Walbaum), in the Columbia River Basin, USA. Anadromous fish (steelhead, Chinook salmon O. tshawytscha [Walbaum]) abundance, juvenile steelhead abundance and habitat conditions were not significantly different between paired reaches (i.e. upstream and downstream of former barrier sites), suggesting these sites are no longer full barriers to movement. This suggests that barrier removal projects on small Columbia Basin streams provide adequate fish passage, increased habitat availability and increased juvenile anadromous fish abundance immediately upstream of former barriers.